2013
DOI: 10.1371/journal.pone.0054956
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Characteristics of Forest Fragments Determine Specialisation of Plant-Frugivore Networks in a Mosaic Forest Landscape

Abstract: Plant-frugivore networks play a key role in the regeneration of sub-tropical forest ecosystems. However, information about the impact of habitat characteristics on plant-frugivore networks in fragmented forests is scarce. We investigated the importance of fruit abundance, fruiting plant species richness and canopy cover within habitat fragments for the structure and robustness of plant-frugivore networks in a mosaic forest landscape of South Africa. In total, 53 avian species were involved in fruit removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 46 publications
(63 reference statements)
1
19
1
Order By: Relevance
“…Our results reveal large‐scale variability in interaction complementarity, estimated from specialization, as shown by other studies over regional extents (e.g., Chama et al, ). Local specialization values differed significantly from those expected by the random association of interacting frugivores and plants, suggesting that interaction complementarity resulted from ecological determinants (Dormann et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Our results reveal large‐scale variability in interaction complementarity, estimated from specialization, as shown by other studies over regional extents (e.g., Chama et al, ). Local specialization values differed significantly from those expected by the random association of interacting frugivores and plants, suggesting that interaction complementarity resulted from ecological determinants (Dormann et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Consistently, an experimental study with nectar feeders in tropical forests showed a low specialization of hummingbird species under manipulated unlimited nectar resources, whereas the same hummingbird species partitioned their foraging niches under natural conditions with limited resources (Maglianesi et al ). However, increasing specialization when resource availability is low is not consistent with other studies of mutualistic seed‐dispersal (Albrecht et al , Chama et al ) and pollination networks (Fontaine et al ) which found increasing specialization with greater resource abundance. These results were interpreted using optimal foraging theory which assumes that at low resource abundance species tend to widen their foraging niche, due to a higher cost in foraging for specific resources (MacArthur and Pianka ).…”
Section: Discussioncontrasting
confidence: 54%
“…Invaded forests in our study region still seem to sustain habitat conditions, which are suitable for forest specialists (e.g. high fruiting plant richness and dense canopy covers; Chama et al 2013). An explanation is that invasive plants mainly dominated at forest edges, whereas the forest interior often still showed near‐natural conditions.…”
Section: Discussionmentioning
confidence: 86%